NEGOTIATING CURRICULUM STANDARDS: TEACHER AUTONOMY IN ISLAMIC SCHOOL CONTEXTS - Khudori, Ahmad (UHN IGB Sugriwa Denpasar, 2026)
Teacher autonomy plays a crucial role in shaping instructional practices, particularly within Islamic schools where educators are required to balance national curriculum standards with religious, moral, and cultural values. This study explores how English teachers in Islamic boarding schools manage the pressures of curriculum standardization while maintaining professional autonomy in their classrooms. Adopting a qualitative case study design, data were collected through classroom observations and semi-structured interviews with four English teachers affiliated with the Musyawarah Guru Mata Pelajaran (MGMP) at the Madrasah Aliyah level in East Java, Indonesia. The participants were selected based on specific criteria, including teaching experience, institutional context, and academic background. The data were analyzed using thematic analysis to identify recurring patterns and meanings related to teacher autonomy. The findings reveal three main themes: (1) contextual and value-integrated teaching approaches, where teachers adapt instructional content to align linguistic goals with Islamic values; (2) adaptive teaching strategies, which include flexible pedagogical methods and selective use of technology to respond to classroom needs; and (3) holistic assessment and skill development, emphasizing formative and reflective evaluation beyond standardized testing. These findings indicate that teacher autonomy in Islamic schools extends beyond instructional freedom to include professional judgment in integrating moral-spiritual objectives with curricular demands. The study concludes that supportive institutional environments, culturally responsive professional development, and flexible curriculum interpretation are essential for strengthening teacher autonomy. The findings offer practical insights for policymakers and school leaders seeking to improve teacher professionalism and instructional quality in religious educational contexts.